THE NEED for BIBLIOTHERAPY SERVICES IN LITHUANIAN PUBLIC LIBRARIES - JANAVIČIENĖ, DAIVA (Knygotyra, 2011)
The aim of the study was to analyse the feedback from participants of events held in libraries on the need for bibliotherapy service and access of the service in libraries and to explore the impact of the newly acquired knowledge on the opinion change. The study used observation, interview and group questionnaire survey methods, involving the participants of three bibliotherapy events in Skuodas, Mažeikiai and Šiauliai public libraries. Qualitative data analysis included data organization, grouping, searching for causal relations, comparing the first and repeated questionnaire data, determining the reliability of data and the opinion dynamics. Respondents: prior to the event, 140 questionnaires were handed out, and 108 were returned filled in; after the event 140 questionnaires were distributed and 129 were returned. The re-poll conducted after a short period of time, when the opinion was influenced by the newly obtained knowledge, reflects the reliability / unreliability of the main trends and expresses the dynamics of opinion change, born by the externalities – the information provided by a lector. There is not much articles on bibliotherapy in Lithuanian scientific or popular press. Lately, there is an increased need for such information, as shown by the abundant educational – informational events concerning bibliotherapy. The work partially fills this gap by summarizing the scientific and bibliotherapeutic service situation in Lithuanian libraries. The study analyses data collected during events in three different areas of Lithuania. The data may not reflect the trends of the country; in this case, the study should be regarded as a pilot one, expressing the general aspects which in other areas may occur in different ways. It has been found that the greatest incentive to participate in bibliotherapy for librarians is the desire of more knowledge that they could use in their work and personal development. It is important to note that among the reasons for participation in the event, a significant amount of responses (18%) included the situation at work – activities when the use of bibliotherapy could be useful knowledge. This highlights the need to expand the number of similar events, their coverage, diversity of forms, making it possible to exchange experience, analyse situations, and jointly seek for solutions. The lack of bibliotherapeutic knowledge influenced the opinion of respondents about the service provision. Initial results of the survey indicate that the prevailing opinion of bibliotherapy is associated with theoretical reflections but not with real possibilities to provide the service. During the event, limited information (of 1.5 to 2 hours duration) positively influenced the opinion. The number of respondents with a negative opinion of bibliotherapy service went down, but still survived (2%). This proves that there is a possibility to provide services in bibliotherapy. The librarians named the obstacles and offered the possible solutions. Some are already engaged and committed to providing bibliotherapy services to libraries. At the same time, there remains a clearly expressed opposition to this kind of service. When looking for the possibilities and thinking about the need for bibliotherapy, librarians suggest specific ways, indicating the importance of this service and the reasons for cognitive barriers. The main obstacle for the need of knowledge is the fact that it is not expressed; librarians agree that readers are not aware of service options. In addition, as one participant said, people who need this service are shy. Considering the reason why such a service is required (the environment is full of aggression, various social issues such as immigration, loneliness, people’s reticence and the resulting problems, etc.), librarians are of the opinion that such services are necessary. A theoretical analysis of bibliotherapeutic work has shown that bibliotherapy is considered by scientists and practitioners as a type of reading recommendations and informational activities, or as an educational and cognitive approach. The obtained results show the opinion of participants on the objective need for bibliotherapy services in library and librarians’ and other participants’ opinion on the real possibilities of and obstacles to providing this service in libraries. A repeated survey confirmed the main trends and illustrated the dynamics of a marginal change of opinion toward the positive side. It is likely that the dynamics is a result of the new information. The survey results are based on the opinion of librarians who directly interact with readers and know their needs. Analysis of the readers’ opinion would increase the reliability of the results. In practical terms, there is a lack of methodologies and literature on strengthening the bibliotherapy services in libraries.